Peran Ibu Tunggal Sebagai Warga Binaan LAPAS Perempuan Kelas IIA Semarang dalam Keberlangsungan Ekonomi Keluarga - Lavinialeda Miftachulia; Thriwaty Arsal (Universitas Hamzanwadi, 2026)
The study aims to analyze the economic strategies carried out by single mothers, the forms of social support they receive, and the role of independence development programs in supporting family economic sustainability. This research employs a qualitative approach using case study method. Data were collected through in-depth interviews, participatory observation, and documentation involving five single mothers as key informants and three correctional officers responsible for inmate development programs. Data analysis applied the interactive model, consisting of data reduction, data display, and conclusion verification, supported by source and technique triangulation to ensure data validity. The findings reveal that single mothers develop adaptive economic strategies through participation in prison workshop programs, utilization of work incentives, and alternative income-generating activities such as laundry services and institutional duties. Family support and correctional independence development programs also play a significant role in strengthening family economic sustainability. The study demonstrates that single mothers as inmates are not merely objects of correctional programs, but active social actors who construct adaptive economic strategies within structural constraints. This research reinforces the relevance of AGIL concept, particularly in the aspects of adaptation, integration, goal attainment, and latency in maintaining the economic function of the family.